Assessment of Solid Waste Management in Bhaktapur Municipality - Ranjit, Amit Shankar; Shakya, Ronish; Gwachha, Sushila; Ganesh, Razim; Prajapati, Meera; Bhaila, Puna; Duwal, Indu (Journal of Science and Engineering, 2019)
Bhaktapur Municipality has been performing better to keep the city clean. However, scarcity of space for the land filling of the solid waste and proper segregation of waste at the source has been a hurdle for the Municipality. This paper aims to determine solid waste generation rate and to analyze overall situation of solid waste management of Bhaktapur Municipality. However, the data will not represent the seasonal and occasional variations. Additionally, waste from street-sweeping and large-scale institutional and commercial components of the Municipality has not been assessed. Arkin and Colton (1963) was referred for the sample size determination. Sample of 376 households were taken accordingly. Twenty representative samples each for commercial and institutional establishments were selected, and one each for special cases such as hospital, slaughter house and poultry has been assessed. Municipal household waste generation was found to be 0.093kg per capita per day which was chiefly composed of 77% organic, 18% plastic and 3% paper. Organic waste has been a major waste for institutions such as schools whereas at governmental and public offices, paper is the predominantly generated waste. Among commercial establishments, shops and restaurants mostly generate organic waste and that for departmental stores has been paper. Though collection system was found to be satisfactory, treatment and final disposal have been unsustainable. Available treatment facilities have been shut down whereas other infrastructural components have been lacking.